PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAKUL KARIMAH DI SLB NEGERI GEDANGAN SIDOARJO - Umudah Binti Aisiah; Abdul Jalil; Lia Nur Atiqoh Bela Dina (VICRATINA, 2020)
Education is a very important aspect in human life, education has a basis, function and purpose that strongly emphasizes religious values. So that religious education can be said to be a system of national education. This is because Islamic religious education is one form of efforts to realize the goals of education. The presence of teachers is considered very important in supporting moral development in students. Even more so in the development of morals for students with special needs in special schools. This research is a qualitative research and this type of research is a case study. Data collection techniques through observation, interviews anddocumentation. The focus of research that will be discussed here is how is the process of moral guidance, how is the role of Islamic religious education teachers in moral development, what are the obstacles in moral development that are carried out at SLB Gedangan Sidoarjo. In order to prove to the wider community that children with special needs are not like what the community values so far.